Impact of initiating a PGF2α-GnRH fixed-time AI protocol at the late luteal phase on reproductive performance of repeat-breeder crossbred dairy cattle - Ghuman, S P S; Honparkhe, M; Singh, Jagir (The Indian Journal of Animal Sciences, 2012)
The objectives of this study were to document ovarian and endocrine responses as well as pregnancy establishment following the treatment of repeat-breeder crossbred dairy cattle with a prostaglandin F2a-gonadotropin releasing hormone (PGF2a-GnRH) fixed-time artificial insemination (AI) protocol at the late luteal phase. Cattle (15) were administered PGF2a (500 µg cloprostenol) on day 16 of the estrous cycle, followed by GnRH analogue (20 µg buserelin) 5 days later. About 24 h after GnRH, AI was carried out in all the cattle. Transrectal ovarian ultrasonography was carried out at the time of PGF2a administration, at AI and on days 5, 16 and 21 post-AI. Plasma progesterone was assayed with solid- phase radioimmunoassay. All the cattle responded to treatment with a luteolytic dose of PGF2a. On the day of AI, large follicles of 15.94±0.60 (12.7–22.0) mm diameter were observed in all the cattle. The presence of active luteal profile on day 5 post-AI confirmed the occurrence of ovulation in all the cattle. Post-treatment first service conception rate was appreciable (66.7%) in cattle with history of repeat breeding. Repeat-breeder cattle failing to conceive after hormonal treatment had suprabasal plasma progesterone on the day of AI in comparison to their non-conceiving counterparts. In conclusion, initiation of PGF2a-GnRH protocol based fixed-time AI protocol at the late luteal phase is highly successful for inducing ovulation in all the repeat-breeder cattle, and yielded an appreciably high conception rate.